ANALISIS KESULITAN BELAJAR MASALAH TRANSPORTASI PROGRAM LINIER - Asroni Asroni; Fhela Vhantoria Ningrum; Venty Meilasari (Universitas Muhammadiyah Kotabumi, 2021)
This research aims to describe the mathematics learning difficulty locations and the mathematics learning difficulties types faced by mathematics education students. This research is a mix method research study which used a quantitative and a qualitative approach. This research’s subjects were students of mathematics education in Muhammadiyah university Kotabumi who had learning difficulties on Transportation Problem. The instruments used here were in diagnostic test and interview guide. The locations of learning difficulties viewed based on students’ mistakes/difficulties in completing the diagnostic test. These students categorized as students who were experiencing learning difficulties were interviewed to obtain confirmation regarding the mathematics learning difficulties types. The research result suggests that mathematics learning difficulty locations faced by the research subjects are factual knowledge 4,68%, conceptual knowledge 11,32%, procedural knowledge 10,93%, and metacognitive difficulties 12,5%. The mathematics learning difficulties types faced by the research subjects are fact remembering difficulty 4,69%, concept remembering difficulty 11,33%, fact understanding difficulty 4,69%, concept understanding difficulty 11,33%, concept applying difficulty 11,33%, procedure applying difficulty 10,16% ,fact evaluating diffculty 4,69%, , concept evaluating difficulty 11,33%, procedure evaluating difficulty 10,16%, written metakognitive communicating difficulty 1,25%, fact observing difficulty 4,69%, concept observing difficulty 11,33% and procedure observing difficulty 10,16%.